If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(z + -85) = 56 Reorder the terms: 4(-85 + z) = 56 (-85 * 4 + z * 4) = 56 (-340 + 4z) = 56 Solving -340 + 4z = 56 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '340' to each side of the equation. -340 + 340 + 4z = 56 + 340 Combine like terms: -340 + 340 = 0 0 + 4z = 56 + 340 4z = 56 + 340 Combine like terms: 56 + 340 = 396 4z = 396 Divide each side by '4'. z = 99 Simplifying z = 99
| (x^2+2x)/(2x^3+10x^2+12x) | | 83-w=86 | | 73=62-u | | 90=15+x(3) | | 90=15+(x/3) | | 6-8x=51-29x | | -v+248=174 | | 0.3+0.18= | | 218=105-v | | 278=-v+186 | | -u+233=120 | | 7p+8q=12 | | 5x+12=100 | | 6.47-d=9.77 | | 4(3x+7)-6(4x-7)=10x+3(2x-6) | | 6-4g=18 | | 4k+4=2(6k-14)+64 | | 200-u=119 | | 874=16(b+17)+26 | | x^2+5=10 | | 2(3x+9)=1/8 | | 990=30(k+3) | | 2/3x-19=18 | | 3x-15=21-6x | | (x*x)+(5x)=8 | | -2(w+883)=-546 | | 6y+2=2y+10 | | 0=(2750-400)/5.49 | | x+3x-8=5x-7 | | 15=-3/2v | | -30(p+309)+835=505 | | 3(h-41)-26=55 |